Rotavirus vaccines in Israel: Uptake and impact - Khitam Muhsen; Daniel Cohen (Taylor & Francis Group, 2017)
We present an overview of the impact of universal rotavirus immunization with the pentavalent vaccine, RotaTeq, which was introduced in Israel in 2010. The vaccine is given free of charge at age 2, 4 and 6 months, with an 80% coverage that was shortly achieved during the universal immunization period. Compared to pre-universal immunization years (2008-2010), a reduction of 66-68% in the incidence of rotavirus gastroenteritis (RVGE) hospitalizations was observed in 2011-2015 among children aged 0-23 months in central and northern Israel. In southern Israel a reduction of 80-88% in RVGE hospital visit rate was found among Jewish children aged 0-23 months in 2011-2013. Among Bedouins, the respective decline was 62-75%. A significant reduction of 59% was also observed in RVGE clinic visits, presumably representing less severe illness. Indirect benefit was evident in children aged 24-59 months who were ineligible for universal immunization. Vaccine effectiveness against RVGE hospitalization was estimated at 86% in children aged 6-23 months. Changes in the circulating rotavirus genotypes occurred but the contribution of vaccine induced immune pressure is unclear. Universal rotavirus immunization was followed by an impressive decrease in the burden of RVGE in young children in Israel, likely attributed to good vaccine coverage and effectiveness.